Manajemen Arsip Rekam Medis Sebagai Basis Informasi Pelayanan Kesehatan di Puskesmas Baturaden II - Ahsin, Kahfie Ahmad (SIBER PRESS Universitas SIBERMU, 2025)
Effective healthcare delivery in primary care facilities depends on the availability of accurate, complete, and easily accessible medical information. In this context, the management of medical record archives serves as a central component in determining service quality, particularly in community health centers (Puskesmas) as the frontline of Indonesia’s healthcare system. This study focuses on the management of medical record archives at Puskesmas Baturaden II, examining how archival practices support information availability for clinical decision making, service delivery, and healthcare coordination. This research uses a Qualitative-based Case Study method with Field Research data collection techniques through observation, interviews and documentation related to medical record archive management at Baturaden II Community Health Center. The results indicate that the management of medical record archives at Puskesmas Baturaden II contributes meaningfully to providing an information basis for healthcare services. Keywords: Archive, medical record, puskesmas Baturaden II